Liver cancer with concomitant TP53 and CTNNB1 mutations: a case report - Friemel, Juliane (BMC Clin Pathol, 2016)
BACKGROUND: In the spectrum of molecular alterations found in hepatocellular carcinoma (HCC), somatic mutations in the WNT/β-catenin pathway and the p53/cell cycle control pathway are among the most frequent ones. It has been suggested that both mutations occur in a mutually exclusive manner and they are used as molecular classifiers in HCC classification proposals. CASE PRESENTATION: Here, we report the case of a treatment-naïve mixed hepatocellular/cholangiocellular carcinoma (HCC/CCC) with morphological and genetic intratumor heterogeneity. Within the predominant part of the tumor with hepatocellular differentiation, a p.D32V mutation in exon 3 of the CTNNB1 gene occurred concomitantly with a TP53 intron 7/exon 8 splice site mutation. CONCLUSION: Intratumor heterogeneity challenges the concept of CTNNB1 and TP53 gene mutations being mutually exclusive molecular classifiers in HCC, which has implications for HCC classification approaches.